University Students Approach to Human Papilloma Virus and Vaccine, Knowledge Level Analysis - Elif Uçar; Melih Bestel; Seda Aşcı (İstanbul Medical Journal)
Introduction: In this study, the aim was to evaluate the level of knowledge of university students about human papilloma virus (HPV) and HPV vaccine, to determine their attitudes towards HPV vaccination and the obstacles they face, and to emphasise what needs to be done to increase awareness. Methods: In this descriptive study, participants were administered a structured questionnaire containing questions on HPV infection, types of vaccines, age ranges for vaccination and vaccine efficacy. In addition, the effect of factors such as attitudes towards vaccination, sources of information and the cost of vaccination was also evaluated. Results: The results showed a lack of knowledge about HPV and HPV vaccines among university students. Most of the participants were not sufficiently familiar with the vaccine, and although they had information about HPV infection, they were hesitant about the vaccine’s protective benefits. Cost, lack of information, and confidence in the vaccine were the main reasons for not getting vaccinated. Conclusion: Our study revealed that awareness of HPV vaccination among university students is low and the cost of the vaccine is an important barrier. To implement an effective HPV vaccination programme, awareness-raising activities should be carried out, especially using peer networks and social media. In addition, awareness can be raised through educational programmes and curriculum arrangements.